Information security awareness at the knowledge-based institution: its antecedents and measures - Ahlan, Abdul Rahman; Lubis, Muharman; Lubis, Arif Ridho (Elsevier Ltd., 2015)
Information security awareness (ISA) is referred to as a state of consciousness where user ideally committed to the rules, recognize the potentiality, understand the importance of responsibilities and act accordingly. Despite the number of case occurred in information security breaches, especially at knowledge-based institution result from the reluctance of user's failure to comply with security guidelines, such effective measure should take place to anticipate the negative effect. Therefore, more attention is required to understand the roles of individual, institutional and environmental antecedent for optimization in raising the information security awareness. This paper elucidated the roles of its antecedent and measure in influencing ISA of user using survey method that contributes for better understanding by analyzing user perception. From the result, this study identified several important factor impacts to the awareness and its relationship to other factor such as religious indicator can influence peer performance but also social pressure. Thus higher education can focus the policy for encouraging them to have proper response from student and staff in avoiding security incident.